Pastoral Places and the City: Environmental Rhetoric in Plato’s Phaedrus - Jack Love (Humanities)
Historically, the notion of nature or the place outside the city in Phaedrus has been read as a proto-pastoral dialogue. If we accept this reading of Plato’s dialogue, Phaedrus hierarchizes the landscape where the city is perceived as superior to the noncity. However, I argue that Plato offers an alternative in Phaedrus that opposes the country–city hierarchized binary. Rather than seeing the natural world as a starting place for intellectual knowledge, Plato refuses the pastoral impulse that projects a construction of nature in Phaedrus. Instead, he values the noncity as any other place where individuals can come together in a dialectical fashion to ascertain truth. Indeed, Socrates’ orientation toward the setting in Phaedrus suggests that he is practicing a rhetoric of immersion in the ambient nonhuman place around him before attempting to project meaning onto it.